PERSEPSI PEMUSTAKA TERHADAP PUSTAKAWAN LAYANAN SIRKULASI DALAM MENDUKUNG PELAYANAN PERPUSTAKAAN MODERN DI DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI SUMATERA BARAT - Muhammad Arief; Elva Rahmah (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2026)
This study aims to analyze user perceptions of circulation librarians in supporting modern library services at the Regional Archives and Library Office of West Sumatra Province. This study uses a quantitative descriptive approach. The population consisted of 3,277 circulation service users during the period October–December 2025, with a sample of 97 respondents determined using the Slovin formula and purposive sampling techniques. Data were collected through questionnaires, observations, and documentation studies. Data were analyzed using descriptive statistics by calculating the average value and Respondent Achievement Level (RAL). The results showed that user perceptions of circulation librarians were generally in the good to very good category, with an overall positive assessment of 73.1%. In the SERVQUAL dimension, Tangibles obtained the highest percentage (75.3%), while reliability and assurance showed the lowest percentage (70.1%). In the LibQUAL dimension, the Library as a place obtained the highest score (76.3%), followed by service influence (74.2%) and information control (72.2%). The research results show that circulation librarians have made a positive contribution to supporting modern library services through professional and responsive service supported by adequate facilities and information systems. However, improvements in librarian competency, service consistency, and information system optimization are still needed to continuously improve service quality.